A History of Pigs in China: From Curious Omnivores to Industrial Pork. Issue 4 (November 2020) - Lander, Brian; Schneider, Mindi; Brunson, Katherine
Abstract : Pigs have played a central role in the subsistence and culture of China for millennia. The close relationship between pigs and people began when humans gradually domesticated wild pigs over 8, 000 years ago. While pigs initially foraged around settlements, population growth led people to pen their pigs, which made them household trash processors and fertilizer producers. Household pigs were in daily contact with people, who bred them to fatten quickly and produce larger litters. Early modern Europeans found Chinese pigs far superior to their own and bred the two to create the breeds now employed in industrial pork production around the world, including China. In recent decades, industrial farms that scientifically control every aspect of pigs' lives have spread rapidly. Until recently, most Chinese people ate pork only on special occasions; their ability in recent decades to eat it regularly exemplifies China's increasing prosperity. Meanwhile, vast areas of North and South American farmland are now devoted to growing soybeans to feed hundreds of millions of pigs in China, and the methane, manure, and antibiotic resistance they produce creates environmental and health problems on a global scale.